2009
DOI: 10.1007/s00204-009-0403-5
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental and early life exposure to inorganic arsenic affected development and behavior in offspring rats

Abstract: To evaluate the developmental neurotoxicity of arsenic in offspring rats by transplacental and early life exposure to sodium arsenite in drinking water, the pregnant rats or lactating dams, and weaned pups were given free access to drinking water, which contained arsenic at concentrations of 0, 10, 50, 100 mg/L from GD 6 until PND 42. A battery of physical and behavioral tests was applied to evaluate the functional outcome of pups. Pups in arsenic exposed groups weighed less than controls throughout lactation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…For example, in utero and early life exposure of rodents even to 50 or 100 μg/μL of iAs through drinking water leads to learning and memory deficits in adult offspring [3,13]. In another study, perinatal mice exposure to low iAs concentration (55 μg/L) led to reduced performance in forced swim test and increased response time in learned helplessness [10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in utero and early life exposure of rodents even to 50 or 100 μg/μL of iAs through drinking water leads to learning and memory deficits in adult offspring [3,13]. In another study, perinatal mice exposure to low iAs concentration (55 μg/L) led to reduced performance in forced swim test and increased response time in learned helplessness [10].…”
Section: Introductionmentioning
confidence: 98%
“…iAs and its metabolites are eliminated through urine and feces, but an important proportion of them will accumulate in different tissues, including the brain [2]. iAs and its metabolites accumulate in the cerebral cortex, hippocampus, striatum, midbrain, thalamus, pons, medulla oblongata, and pituitary gland of rodents intoxicated with 2.5, 5, and 10 mg/kg/day of sodium arsenite [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Rodent studies have reported reproducible results showing neurobehavioral and neurophysiological alterations following a developmental arsenic exposure continuing over different periods of time [116][117][118]. In studies conducted under sub-chronic or chronic exposure conditions, rats treated with arsenite from early gestation exhibited behavioral changes with impaired learning/memory ability [117,118].…”
Section: Arsenicmentioning
confidence: 97%
“…In studies conducted under sub-chronic or chronic exposure conditions, rats treated with arsenite from early gestation exhibited behavioral changes with impaired learning/memory ability [117,118]. For instance, rats treated with 36.7 mg/L arsenite from gestation day (GD) 15 through 4 months of age exhibited significant alterations in spontaneous locomotion and poor performance in the delayed alternation test [117].…”
Section: Arsenicmentioning
confidence: 99%
“…19,20) Rats and mice exposed to arsenic during gestation and early childhood exhibit behavioral deficits such as changes in locomotor activity, learning, memory, depression-like behavior and neuromotor reflex. [21][22][23] The development of the central nervous system (CNS) in neonatal rats is also affected by arsenic, and exposure to arsenic has been shown to cause neuronal death in the adult rat brain. 24) Sodium arsenite at a concentration of 5 µM induces cytotoxicity at a cellular level via acting as a sulfhydryl reagent, which binds to the free thiol groups of numerous enzymes, inhibiting their functions and depleting levels of glutathione (GSH), thus destroying cell metabolism.…”
Section: Sodium Arsenite Induces Neural Cell Death Via a Mitochondriamentioning
confidence: 99%